Gelagat Kepatuhan Zakat Pendapatan Gaji Di Kalangan Kakitangan Awam Persekutuan Negeri Kedah - Kamil, Md. Idris (2002)

(untitled)
Compliance level of zakah on employment income is very low, although such income has long been fatwa and gazetted as obligatory by many states in Peninsular Malaysia. However, there is no study done on the compliance behaviour of zakah on employment income. Thus, this study attempts to investigate factors that influence the compliance behaviour. The first objective of this study is to identify dimensions in attitude towards zakah on employment income. Besides influencing the compliance behaviour, attitude is believed to be a complex construct and therefore, it needs to be studied further in some detail. The second objective is to develop a compliance behaviour model of zakah on employment income. This is to gain understanding as to how the variables involved influence the compliance behaviour. Various variables from several disciplines are believed to have significant influence on compliance behaviour. The survey and questionnaire methods were used for collecting data. Principal component and multivariate logistic regression analyses were applied to data collected from 353 respondents, who were selected through systematic sampling. Principal component analysis shows that attitude towards zakah on employment income can be decomposed into five smaller components. Each component, together with other variables, was tested in the compliance behaviour model. Results from the logistic regression analysis show that seven variables are positively associated with the compliance behaviour. These variables are zakah laws; service quality; promotional exposure; three components of attitude; and knowledge. One variable, i.e., religiosity index, is found to be associated negatively. The above findings imply that zakah laws should be strengthened. Further, Baitulmal should try to improve the perception of the ummah concerning its service quality, and revamp its zakah promotion strategies. Since, attitude, religiosity, and knowledge on zakah are also important factors in the compliance behaviour, they need to be improved in order to increase the level of compliance. Except for religiosity, the results show that, the more positive the variables, the higher is the potential of zakah compliance. The negative result from the religiosity index suggests that many respondents still prefer to pay zakah unofficially, being under the influence of certain individuals who disagree with thefatwa of zakah on employment income. Attitude towards zakah on employment income was indeed a complex variable, which should be first decomposed, in order to conduct further study on it. By doing so, the goodness of fit of the zakah compliance model was improved and a more informative model was obtained.